Decolonizing trauma studies: Trauma and postcolonialism - Andermahr, Sonya (MDPI AG - Multidisciplinary Digital Publishing Institute, 2016)
This Special Issue aims to explore the complex and contested relationship between Trauma Studies and postcolonial theory, focusing on the possibilities for creating a decolonized trauma theory that takes account of the suffering of minority groups and non-Western cultures, broadly defined as cultures beyond Western Europe and North America. The issue builds on the insights of, inter alia, Stef Craps's book, Postcolonial Witnessing, and responds to his challenge to interrogate and move beyond a Eurocentric trauma paradigm.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; discours dominant; décolonialisme; périodes historiques; ressource en ligne; système colonial; systèmes d'oppressions; trauma

Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Les femmes dans les professions scientifiques au Canada - Dionne-Simard, Dominique; Galarneau, Diane; LaRochelle-Côté, Sébastien (2016)
Le présent article fournit des renseignements sur les femmes âgées de 25 à 64 ans qui occupent des professions dans le domaine des sciences naturelles et appliquées (soit les professions scientifiques) au Canada, à l’aide des données des recensements de 1991 et 2001 et de l’Enquête nationale auprès des ménages (ENM) de 2011. Les conditions d’emploi des hommes et des femmes dans ces professions y sont également examinées au moyen de données provenant de l’Enquête sur la population active (EPA). • De 1991 à 2011, la part des femmes occupant une profession scientifique requérant des études universitaires est passée de 18 % à 23 %, et elle est passée de 14 % à 21 % dans les professions scientifiques de niveau collégial. • Au cours de la même période, la proportion de femmes est passée de 59 % à 65 % dans les professions non scientifiques de niveau universitaire, et de 41 % à 44 % dans les autres professions non scientifiques de niveau collégial. • Les femmes étaient à l’origine de 27 % de la croissance totale des effectifs dans les professions scientifiques de niveau universitaire observée de 1991 à 2011, mais de 75 % de la croissance des effectifs dans les professions non scientifiques de niveau universitaire. • Environ 60 % de la croissance des effectifs dans les professions scientifiques de niveau universitaire était attribuable au domaine de l’informatique. La contribution moindre des femmes à la croissance totale des effectifs dans les professions scientifiques est liée à leur faible représentation dans le secteur de l’informatique. • Les conditions d’emploi sont plus avantageuses pour les travailleurs occupant une profession scientifique. Toutefois, parmi ceux qui travaillaient à temps plein, les hommes gagnaient 9 % de plus que les femmes en moyenne, à la fois dans le secteur scientifique et le secteur non scientifique
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; femmes* scientifiques; inégalités; inégalités hommes-femmes; inégalités salariales; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences